PENJADWALAN TENAGA KERJA HSE MENGGUNAKAN METODE MONROE DI SUMUR EKSPLORASI TAMBUN PT PERTAMINA EP - Antoni Lubis; Nelson Pardede (JURNAL GAUNG INFORMATIKA, 2016)
PT Pertamina EP is a company engaged in the exploration, exploitation and sale of oil and gas products. PT Pertamina EP assigns HSE Coordinators and HSE Coach to carry out safety supervision in every drilling activity. However, scheduling carried out previously by the company is considered unfair because there are still many workers whose working days exceed 2 weeks. So that the calculation is done using the Monroe method. Where previously at each location the workforce needs were 3 people each month, after calculation using the Monroe method it was found that each location needed a workforce of 6 people. So that each worker gets 2 weeks of work and time off in sequence so that the drilling process can be monitored continuously.